Foreign Consulates in Bosnia-Herzegovina and Harmful Activities of European Diplomats (Prilozi za orijentalnu filologiju, 2017)
In all periods of history the European states were interested in Bosnia-Herzegovina. The country was under the domination of the Ottoman Empire during four and a half centuries i.e. between 15th and 20th centuries. Austria, France, Prussia, England, Italy and Russia carried out their commercial activities here and opened many consulates during the 19th century. Austrian Government especially founded Head Consulate, Consulate or Deputy Consulate in all the strategic cities of the region, and thus it reached higher diplomatic representation power in a foreign environment than the other governments. The foreign consuls began intensive dividing and destructive activities in Bosnia-Herzegovina because of the directives from their governments and by using the political chaos in the Ottoman Empire. Austrian consuls were pioneers of these harmful activities. They supported occupation in 1878 and annexation of Bosnia-Herzegovina by Austro-Hungarian Government in 1908. Namely, Austria-Hungarian state occupied Bosnia-Herzegovina first by its consuls, later on by its soldiers. Austria considered the legal rights of the Ottoman Empire in Bosnia Herzegovina as absent, and it dominated between 1878 and 1908. It could solely authorize consul appointments to the region. The other European consuls in Bosnia-Herzegovina also had important missions in the name of their governments. However, diplomatic developments after 1878 in Bosnia-Herzegovina created dismay among all of the foreign consuls and employees apart from Austrians. These consuls recorded harmful activities of Austrian soldiers and officials in the reports they sent to their governments.